PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. JIWA TEKNO KULTURA CIPETE JAKARTA SELATAN - Andi Sopandi (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purpose of this study was to determine the effect of leadership style and work motivation on employee job satisfaction at PT. The soul of Tekno Kultura Cipete, South Jakarta, either partially or simultaneously. This type of research used is causal associative with a quantitative approach. The population in this study were employees of PT. The soul of the techno culture of Cipete, South Jakarta. The sampling technique used was saturated sampling technique and the sample obtained in this study amounted to 63 respondents. The data collection technique is a questionnaire, while the data analysis uses validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, coefficient of determination analysis and hypothesis testing. The results of this study indicate that Leadership Style (X1) has a positive and significant effect on employee job satisfaction, this is seen in the results of the t-test on the Leadership Style variable of 7.502 with a significant value of 0.000 and t-table df=61 of 2,000. Work Motivation (X2) has a positive and significant effect on Employee Job Satisfaction, this can be seen from the results of the t-test on the Work Motivation variable of 5.312 with a significant value of 0.000 and t-table df=61 of 2,000. Leadership Style (X1) and Work Motivation (X2) have a simultaneous and significant effect on employee job satisfaction, this can be seen from the results of the f test of 28,503 with a significant value of 0.000 and an f-table of 3.150. Leadership Style (X1) and Work Motivation (X2) have an effect on Employee Job Satisfaction (Y) by 48.7%, this is based on the acquisition of an R-Square value of 0.487 or 48.7%. While the remaining 51.3% is influenced by other factors not examined.